2015
DOI: 10.1186/s12889-015-2475-x
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of three components of a syndromic surveillance system for the early warning of epidemics in rural China

Abstract: BackgroundSyndromic surveillance systems (SSSs) collect non-specific syndromes in early stages of disease outbreaks. This makes an SSS a promising tool for the early detection of epidemics. An Integrated Surveillance System in rural China (ISSC project), which added an SSS to the existing Chinese surveillance system for the early warning of epidemics, was implemented from April 2012 to March 2014 in Jiangxi and Hubei Provinces. This study aims to measure the costs and effectiveness of the three components of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…A systematic review tracking the efficacy of school-based surveillance systems concluded that such systems could provide one to two weeks of lead time, with high reliability, for the diagnosis of influenza outbreaks (Donaldson et al, 2021). However, we did find one study with mixed results related to school absenteeism data (Ding et al, 2015). The authors surveilled for several diseases of concern, including acute respiratory infectious diseases and gastrointestinal infectious diseases, using symptom data from health facilities, absenteeism data from primary schools (dates, numbers, ages, gender, classes, addresses, reasons for absence, and diseases or symptoms), and sales of selected medicines from pharmacies.…”
Section: Absenteeism Datamentioning
confidence: 67%
“…A systematic review tracking the efficacy of school-based surveillance systems concluded that such systems could provide one to two weeks of lead time, with high reliability, for the diagnosis of influenza outbreaks (Donaldson et al, 2021). However, we did find one study with mixed results related to school absenteeism data (Ding et al, 2015). The authors surveilled for several diseases of concern, including acute respiratory infectious diseases and gastrointestinal infectious diseases, using symptom data from health facilities, absenteeism data from primary schools (dates, numbers, ages, gender, classes, addresses, reasons for absence, and diseases or symptoms), and sales of selected medicines from pharmacies.…”
Section: Absenteeism Datamentioning
confidence: 67%
“…This poses a major challenge to identifying outbreaks and underscores the need for improved, sustainable surveillance for enteric fever. The initial high capital cost of improving surveillance capacity may be balanced by the cost savings and health benefits wrought by early detection and accurate outbreak burden identification [54].…”
Section: Discussionmentioning
confidence: 99%
“…These costs are incurred to develop the capability to acquire and work with data from a new source; recruit, implement, and maintain each data provider; and process, monitor, and respond to the new data. 69 Similar tasks are completed when new data elements are added to existing data streams. Costs are also incurred in training staff members when new data are made available.…”
Section: Recommendationsmentioning
confidence: 99%